2012
DOI: 10.1160/th11-09-0611
|View full text |Cite
|
Sign up to set email alerts
|

Infections and inflammatory diseases as risk factors for venous thrombosis

Abstract: SummaryInflammation and venous thrombosis are intertwined. Only in the recent 15 years clinical epidemiological studies have focussed on inflammatory or infectious diseases as risk factors for venous thrombosis. Although a few reviews and many case reports or studies on these topic has been written, a review reporting relative or absolute risks for venous thrombosis has not been published yet. We performed a systematic review using Medline, Pubmed and Embase and found 31 eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(46 citation statements)
references
References 69 publications
2
43
0
1
Order By: Relevance
“…Tichelaar et al . also demonstrated that the relative risk of VTE rises to 1.9–2.7 during pneumonia and to 1.8–2.1 during a urinary tract infection, in comparison to patients without infection 413. In contrast, a study of the perioperative period conducted by Donze et al .…”
Section: Introductionmentioning
confidence: 92%
“…Tichelaar et al . also demonstrated that the relative risk of VTE rises to 1.9–2.7 during pneumonia and to 1.8–2.1 during a urinary tract infection, in comparison to patients without infection 413. In contrast, a study of the perioperative period conducted by Donze et al .…”
Section: Introductionmentioning
confidence: 92%
“…Finally, inflammatory conditions such as obesity are associated with elevated plasma levels of certain coagulation factors, such as fibrinogen, von Willebrand factor, and factor VIII [20]. These effects are likely mediated by actions of inflammatory cytokines on hepatocytes and endothelial cells.…”
Section: Major Prothrombotic Pathways In Obesitymentioning
confidence: 99%
“…Also, a recent case-control study found that patients hospitalised with infection had a 5- to 12-fold increased risk for VTE within 2 weeks after infection compared to population controls, and that this risk increase waned over time but remained significantly elevated for up to 1 year [6]. Cohort studies with long-term follow-up of VTE-risk after infection are sparse [2], [7], and none has included a comparison group. Previous studies have also lacked microbiological confirmation of infection, which may lead to a falsely inflated association due to possible misdiagnosis of VTE as skin infection or pneumonia.…”
Section: Introductionmentioning
confidence: 99%